Influence of Work-Life Quality on Turnover Intention among Jakarta Millennials—Mediated by Organizational Commitment - Karjadidjaja, Francesca, Ms.; Panggabean, Hana (Psychological Research on Urban Society, 2023)
The current workforce in organizations is heavily dominated by millennials, who have high turnover tendencies. Several studies have revealed a strong link between how urban millennials perceive their quality of work-life and their company loyalty. Furthermore, the level of organizational commitment (OC) has been consistently associated with employee turnover intentions (TI). Based on previous studies, OC serves as a mediating variable for the influence of quality of work-life (QWL) on TI. This study applies three online questionnaires—the QWL Evaluation Scale, the OC Questionnaire, and the Intention to Leave Scale. A convenience sampling technique is applied to sample 280 millennial employees (born from 1983 to 1998) in Jakarta. The data were analyzed with a regression-based mediation analysis method using PROCESS macro in SPSS. Our results reveal that the indirect effect of QWL on TI via affective and normative commitment is significant. It is also found that the mediating role of these two OC dimensions is partial. We recommend that retention strategies should be implemented to improve millennials’ OC.